Harmonic decomposition of two particle angular correlations in Pb-pb collisions at √sNN=2.76 TeV* - Aamodt, Kenneth; Busch, Oliver; Böttger, Stefan; Breitner, Timo; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Kebschull, Udo; Klein, Jochen; Krawutschke, Tobias; Kweon, MinJung; et al. (Physics letters, 2012)
Angular correlations between unidentified charged trigger (t) and associated (a) particles are measured by the ALICE experiment in Pb-Pb collisions at sNN=2.76 TeV for transverse momenta 0.25<pTt,a<15 GeV/c, where pTt>pTa. The shapes of the pair correlation distributions are studied in a variety of collision centrality classes between 0 and 50% of the total hadronic cross section for particles in the pseudorapidity interval |η|<1.0. Distributions in relative azimuth Δϕ≡ϕt−ϕa are analyzed for |Δη|≡|ηt−ηa|>0.8, and are referred to as “long-range correlations”. Fourier components VnΔ≡〈cos(nΔϕ)〉 are extracted from the long-range azimuthal correlation functions. If particle pairs are correlated to one another through their individual correlation to a common symmetry plane, then the pair anisotropy VnΔ(pTt,pTa) is fully described in terms of single-particle anisotropies vn(pT) as VnΔ(pTt,pTa)=vn(pTt)vn(pTa). This expectation is tested for 1⩽n⩽5 by applying a global fit of all VnΔ(pTt,pTa) to obtain the best values vnGF(pT). It is found that for 2⩽n⩽5, the fit agrees well with data up to pTa∼3-4 GeV/c, with a trend of increasing deviation as pTt and pTa are increased or as collisions become more peripheral. This suggests that no pair correlation harmonic can be described over the full 0.25<pT<15 GeV/c range using a single vn(pT) curve; such a description is however approximately possible for 2⩽n⩽5 when pTa<4 GeV/c. For the n=1 harmonic, however, a single v1(pT) curve is not obtained even within the reduced range pTa<4 GeV/c.